Active-Only Current Controlled Summing/Difference Amplifiers Using CCCIIs - Sudhanshu Maheshwari (Active and Passive Electronic Components)
Novel active-only summing/difference amplifiers employing only current controlled conveyors (CCCIIs) are presented. The circuits possess high input impedance, current controllable gain, good linearity and dynamic range, low THD and are suited for IC implementation. SPICE simulation results are included to verify the circuits.